Ocorrência de ectoparasitos em ruminantes do município de Felipe Guerra, Estado do Rio Grande do Norte - Cruz, Lidia Mayara da Costa (Universidade Federal Rural do Semi-Árido, 2019)
The breeding of goats, sheep and cattle is an activity exploited in all continents, in the Northeast region of Brazil, this agricultural activity has significant social and economic importance, since it is closely linked to the promotion of employment and income of the population. Nevertheless, the exploratory system of creation of these animals favors the emergence of ectoparasitoses that promotes great loss in animal productivity. The objective of the research was to identify the occurrence of ectoparasites in ruminant herds of the municipality of Felipe Guerra, State of Rio Grande do Norte. The collections were carried out from February 2018 to March 2019 in goats, sheep and cattle from rural settlements, where biological material was collected manually from 10% of the animals found, for each species, separating them by gender and by age. The material was processed and analyzed in the laboratory and the specimens were identified by means of brackets for classification with microscopy and stereomicroscopy. The results were 354 animals, 122 sheep, 169 goats and 63 cattle, of which 52.3% (185/354) were negative and 47.7% (169/354) positive. Being the only positives of the caprine species for diagnosis of Damalia caprae. It is concluded that the occurrence of ectoparasites in the studied region was diagnosed exclusively in goats, and that health management measures need to be adopted.
Keywords: Ectoparasitose animal; Pecuária; Epidemiologia; Ruminantes; Animal ectoparasitosis; Livestock; Epidemiology; Ruminants; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA